Conjugation and Characterization of Latex Particles with Toxoplasma gondii-specific Immunoglobulin Y Antibodies for Diagnostic Aim and Evaluation Efficiency in In Vitro Culture - Cakir-Koc, Rabia; Budama-Kilinc, Yasemin; Ustun, Eslin; Babur, Cahit (ELSEVIER SCIENCE INC, 2020)
Toxoplasma gondii is a parasite that causes severe health problems in the world. Toxoplasmosis, an infection caused by T. gondii, leads to high risk of mortality in patients with immunodeficiency, transplantation, and cancer. Besides that, it causes miscarriages in pregnancy, various abnormalities such as hydrocephalus in infants and congenital diseases. Because the clinical indication of the disease is not specific, it is confused with many diseases, and this leads to the necessity of directly detecting the presence of the toxoplasmosis. Therefore, various diagnostic assays are needed for the diagnosis of the disease. Amongs them, latex agglutination assay is widely used for the detection of specific antibodies or antigens in samples. Latex particles are coated with immunogenic molecules (antigens) to detect antibodies in the blood or used to identify antigens when coated with specific antibodies. In both, aggregation of latex particles results in agglutination. Monoclonal antibodies are often used in latex agglutination assay as in other diagnostic methods. However, monoclonal antibodies can be produced in low quantities at a high cost. Besides, to produce monoclonal antibodies, an experienced staff, a well-equipped cell culture laboratory, a long period of time, and a burdened budget are needed. In recent years, as an alternative to monoclonal antibodies, immunoglobulin Y (IgY) antibodies, which are obtained from chicken eggs, and specifically produced against desired antigenic constructs, have become quite attractive in terms of both low cost and abundant production without requiring infrastructure. In contrast, the latex assay based on IgY antibodies for use in the diagnosis of T. gondii has not been developed. This study aimed to conjugate T. gondii-specific IgY antibodies to latex particles, characterize the particles by Fourier transform infrared spectroscopy, scanning electron microscopy, and spectroscopic methods, and finally demonstrate the interaction with T.gondii parasites in culture with scanning electron microscopy analysis. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Toxoplasma gondii; IgY; Antibody; Diagnosis; Latex agglutination assay; ELISA; Veterinary Sciences